Measuring solar neutrino fluxes in direct detection experiments in the presence of light mediators - Shuo-yu Xia (Nuclear Physics B)
The potential of the dark matter direct detection experiments to provide independent measurements on solar neutrino fluxes in the Standard Model and in the presence of the light mediators is studied in this work. We also present the sensitivity of direct detection experiments on light mediators with solar neutrinos. We find that the sensitivities on 8B and pp neutrino fluxes can reach ±10% with improved backgrounds and systematic uncertainties and they can be further pushed to ±3% with a increased exposure. The constraints on light mediators can reach O(10−6) for the masses of scalar and vector mediators below 10 MeV. However, the presence of scalar or vector mediators could lead to shifts in the best fit value of 8B fluxes, which will increase the challenges in the precise measurements of solar neutrino fluxes with direct detection experiments.